2021
DOI: 10.2176/nmc.oa.2020-0438
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Study of Primary Brain Tumors in Miyazaki Prefecture: A Regional 10-year Survey in Southern Japan

Abstract: The increased use of neuroimaging and the aging of society have changed the incidence and proportion of histological types of intracranial tumors in Japan. A population-based epidemiological survey has been reported only from Kumamoto Prefecture. We performed a 10-year survey in Miyazaki Prefecture to compare our findings with the incidence rate (IR) of primary intracranial tumors (PIT) reported in the Kumamoto survey. Our study included 1915 new cases of PIT diagnosed in Miyazaki Prefecture between 2007 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In contrast, the ASR of high-grade gliomas in China was 1-4 28 . The overall glioma ASRs were 2.76 and 2.89 in Kumamoto and Miyazaki prefectures respectively 29,30 . The Korean population also showed a similar ASR of 2.82 31 .…”
Section: Incidence Of Gliomasmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, the ASR of high-grade gliomas in China was 1-4 28 . The overall glioma ASRs were 2.76 and 2.89 in Kumamoto and Miyazaki prefectures respectively 29,30 . The Korean population also showed a similar ASR of 2.82 31 .…”
Section: Incidence Of Gliomasmentioning
confidence: 97%
“…An ASR of 0.85 was reported in Taiwan, a province of China 19 . In Japan, the ASR was 1.26 in Miyazaki prefecture 30 . Four Korean studies reported ASR values of 0.59, 0.77, 0.87, and 1.11 ( Figure 2A ) 18 , 31 , 41 , 42 .…”
Section: Epidemiology Characterizationmentioning
confidence: 99%
“…Such a broad‐ranging frequency might be related to both the small size of the series and to the different inclusion criteria. These figures in CS are notably higher than the global incidence rate of 7.9/100 000/year reported in recent epidemiological studies 27,28 . The fact that eight out of the 19 CS patients had multiple meningiomas (Table 1) reinforces such a predisposition in this syndrome.…”
Section: Discussionmentioning
confidence: 64%
“…These figures in CS are notably higher than the global incidence rate of 7.9/100 000/year reported in recent epidemiological studies. 27,28 The fact that eight out of the 19 CS patients had multiple meningiomas (Table 1) reinforces such a predisposition in this syndrome. Our report and literature review support previous claims about the inclusion of meningiomas within the CS consensus diagnostic criteria.…”
Section: Discussionmentioning
confidence: 69%
“…These can also be divided into primary tumors, which originate inside the brain, and secondary tumors, which typically spread from cancers outside the brain and are referred to as brain metastasis tumors. As per [9] in the world, Glioma, meningioma, and pituitary tumors are common primary tumors with occurrence percentage as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 98%